Анализ успешности интродукции декоративных луковичных геофитов природной флоры в Донецком ботаническом саду НАН Украины - Павлова, М.А. (Промышленная ботаника, 2006)
The article presents the analysis results of introduction successfulness assessment of fourty species of ephemeroidous geophytes, belonging to Hyacinthaceae and Liliaceae families of different ecological and geographical distribution. It is determined, that the greatest adaptation potential is peculiar to bulb rosellate geophytes of Hyacinthaceae family, naturally growing on stony slopes of mountains and in woods of Iranian-and-Turanian, and Mediterranean floristic areas.